The correlation between the mother's knowledge about toddler growth and development with the compliance of the mother's visit - Arifah, Siti; Pebriana, Ni Putu Sasmita (International Journal of Health Science and Technology, 2023)
Good maternal knowledge will affect how mothers care for their children’s health, nutrition and monitor their child's growth and development. One of the strategies carried out is to bring toddlers to Posyandu. The regularity of mothers visiting Posyandu will be very useful in monitoring the early detection of toddlers' growth, development, and health status so that mothers know the abnormalities of their children. This study aims to find out how mothers' knowledge about toddler growth and development with the compliance of mothers visiting Posyandu. This study used a correlational quantitative method with a cross-sectional approach. With the Saturated Sample Technique, the entire research sample was used as research respondents, as many as 30. The instrument used is a questionnaire. Primary data collection from questionnaires and secondary data was based on mothers' MCH/KMS books and Posyandu records. Data analysis using Chi-Square statistical test. The study results obtained an alternative value of the Chi-Square test, namely Fisher's Exact Test, with a p-value= 1,000, which means there is no correlation between the two variables. The mother's level of knowledge about toddler growth and development has nothing to do with the mother's obedience or disobedience to visit the posyandu regularly every month.